Conceptual approaches to create control mechanism by passenger commutation services - Zadoya, V. O. (Science and Transport Progress, 2011)
In the article the basic approaches of improving a management mechanism for passenger suburban railway transportations are considered, and the classification of reformation models for passenger suburban railway transportations depending on scales, degree of independence, department subordination and amount of proprietors of future company is offered.